PENERAPAN METODE PERMAINAN KOKAMI BERDASARKAN LKPD SAINTIFIK DALAM MODEL QUANTUM LEARNING TERHADAP KOMPETENSI IPA PESERTA DIDIK KELAS VII SMPN 31 PADANG - Siska Fitri Alwi; Murtiani Murtiani; Letmi Dwiridal (PILLAR OF PHYSICS EDUCATION, 2015)
This research is done because teaching materials student worksheet oriented scientific approach and learning method are less interesting this time, including in SMPN 31 Padang. Curriculum change requires teachers to be able to utilize the entire potential of learners in learning, so that learning centered on the learner. One approach that relates to these demands is scientific approach, for learning can be well with applied so that is needed learning materials, model and method that support the learning process. The purpose of this research is to investigate the influence of applied Method Kokami Game based student worksheet Scientific in Quantum Learning Model for Science Competency of learners of Class VII SMPN 31 Padang. The research is quasi eksperiment with randomized control group only design. The population of this research was Learners of class VII SMPN 31 Padang registered the second semester of academic year 2014/2015. Sampling was done by purposive sampling technique. The research data includes three competency, its are knowledge competency, attitude competency, and skill competency. The research is a written test for knowledge competency, observation sheet for attitude competency and scoring rubric for assessing the performance of skill competency. Analysis of the data for the knowledge competency, attitude competency and skill competency is done by testing  two average. Based on test of normality and homogeneity has be done then test of two average is t-test for knowledge competency and skill competency and t’-test for attitude competency. Data analysis knowledge competency gets an average value 83.67 of experimental class is higher than the control class 78.25. An average value for attitude competency of experimental class 83 and control class 79 while at skill competency, get’s an average value 79.9 of experimental class is higher than control class average 59.6. Analysis of the average similarity test that is done is t-test for knowledge competency and skill competency, t-test for attitude competency.Based on research result It can be concluded that the hypothesis in this research there is significant differences in the applied method of Kokami Games student worksheet Scientific in Quantum Learning Model for science Competency of learners of based Class VII SMPN 31 Padang for knowledge competency and skill competency are recepted but for attitude competency rejected at  real level of 0.05